Climate change and biodiversity - Lovejoy, Thomas E.; Hannah, Lee Jay (Yale University Press, 2005)
"In the past, climate changes have had dramatic repercussions, including large numbers of extinctions and extensive shifts in species ranges. As human-induced climate change accelerates, scientists and policymakers involved with biodiversity conservation need authoritative information in order to design effective plans and responses. Climate Change and Biodiversity meets this need. Written for the specialist as well as the concerned citizen, this important book presents a comprehensive view of the newest research and thinking on climate change and biological diversity."--Book Jacket.